Model of a conflict situation in information security management - Домарєв, Дмитро Валерійович; Милокум, Яна Валеріївна (Ukrainian Information Security Research Journal, 2015)
The problem of information security managementemerged from the necessity to search for the ways toincrease the efficiency of the state information systemsfunctioning in modern conditions. To choose the adequatecounteractions to the information security threatsand attacks, it was recommended to apply the models ofconflict parties’ interaction and the models of conflictsituations in the conditions of vagueness. Conflict situationsin the information security management of the statewere modelled using strategically-probabilistic approach.The process of conflict was described as a variable processwith two states and known transition matrix. Formulaswere derived to calculate the interval transition probabilities between the states of attack and defence. Themodel of conflict situations in information security managementwas created. Due to formalization of the processof information security management system reaction toattacks, the automated forecasting was achieved for theintervals of safety and information security recovery durationafter attacks.